HTLV Tax: A Fascinating Multifunctional Co-Regulator of Viral and Cellular Pathways - Currer, Robert; Van Duyne, Rachel; Jaworski, Elizabeth; Guendel, Irene; Sampey, Gavin; Das, Ravi; Narayanan, Aarthi; Kashanchi, Fatah (Frontiers in Microbiology, 2012)
Human T cell lymphotropic virus type 1 (HTLV-1) has been identified as the causative agent of adult T cell leukemia (ATL) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). The virus infects between 15 and 20 million people worldwide of which approximately 2 to 5% develop ATL. The past 35 years of research have yielded significant insight into the pathogenesis of HTLV-1, including the molecular characterization of Tax, the viral transactivator and oncoprotein. In spite of these efforts, the mechanisms of oncogenesis of this pleiotropic protein remain to be fully elucidated. In this review, we illustrate the multiple oncogenic roles of Tax by summarizing a recent body of literature that refines our understanding of cellular transformation. A focused range of topics are discussed in this review including Tax-mediated regulation of the viral promoter and other cellular pathways, particularly the connection of the NF-κB pathway to both post-translational modifications of Tax and sub-cellular localization. Specifically, recent research on polyubiquitination of Tax as it relates to the activation of the IkappaB kinase (IKK) complex is highlighted. Regulation of the cell cycle and DNA damage responses due to Tax are also discussed, including Tax interaction with minichromosome maintenance proteins and the role of Tax in chromatin remodeling. The recent identification of HTLV-3 has amplified the importance of the characterization of emerging viral pathogens. The challenge of the molecular determination of pathogenicity and malignant disease of this virus lies in the comparison of the viral transactivators of HTLV-1, -2, and -3 in terms of transformation and immortalization. Consequently, differences between the three proteins are currently being studied to determine what factors are required for the differences in tumorogenesis.